СӨЗЛИК – РУЎХЫЙ ҚӘДИРИЯТ - Байқабылов, У.; Төрткулбаева, Т. (SCIENCE and SOCIETY, 2023)
This article reveals the basic concepts and concepts related to the field of lexicography of Kazakh language education. The scientific activities and theoretical conclusions of Doctor of Philology, Professor M.M. Malbakov were also discussed.